A protease-based biosensor for the detection of schistosome cercariae - Webb, A.J.; Kelwick, R.; Doenhoff, M.J.; Kylilis, N.; MacDonald, J.T.; Wen, K.Y.; McKeown, C.; Baldwin, G.; Ellis, T.; Jensen, K.; Freemont, P.S. (Nature Publishing Group, 2016)
Parasitic diseases affect millions of people worldwide, causing debilitating illnesses and death. Rapid and cost-effective approaches to detect parasites are needed, especially in resource-limited settings. A common signature of parasitic diseases is the release of specific proteases by the parasites at multiple stages during their life cycles. To this end, we engineered several modular Escherichia coli and Bacillus subtilis whole-cell-based biosensors which incorporate an interchangeable protease recognition motif into their designs. Herein, we describe how several of our engineered biosensors have been applied to detect the presence and activity of elastase, an enzyme released by the cercarial larvae stage of Schistosoma mansoni. Collectively, S. mansoni and several other schistosomes are responsible for the infection of an estimated 200 million people worldwide. Since our biosensors are maintained in lyophilised cells, they could be applied for the detection of S. mansoni and other parasites in settings without reliable cold chain access.